Preliminary bench experiment study on working parameters of pneumatic seeding mechanism for wheat in rice-wheat rotation areas - Wang, Chao; Lu, Caiyun; Li, Hongwen; He, Jin; Wang, Qingjie; Cheng, Xiupei (International Journal of Agricultural and Biological Engineering, 2020)
In order to solve the serious problems of soil adhesion and blockage as well as high operating resistance for wheat seeders under the condition of sticky heavy loam clay in rice-wheat rotation area, a new concept of non-contact pneumatic seeding technology that could rip wheat seed into the soil by high pressure accelerating airflow was proposed in this paper. A preliminary bench experiment was conducted and high-speed photography technology was used to study the parameters of wheat pneumatic seeding under five levels (30%, 35%, 40%, 45% and 50%) of soil moisture content for loam clay. Experimental results showed that: wheat seeds could be ripped into soil without damage and acquired varying degrees of germination by way of pneumatic seeding; shooting depth shown a deepening tendency with the increase in shooting velocity, and the value of seeding depth and seeding velocity are closely related to the soil moisture level, which wheat seeds can achieve higher shooting depth with relative lower shooting velocity when the soil moisture content increases continuously; none of wheat seeds could be ripped into the soil with about 2.93 m/s shooting velocity that accelerated in the form of free fall, while the shooting velocity that wheat seeds needed in order to be completely ripped into soil with 3 mm shooting depth were 40- 50 m/s (30% soil moisture content), 30-40 m/s (35% soil moisture content), 20-30 m/s (40% soil moisture content), 10-20 m/s (45% soil moisture content) and 2.93-10 m/s (20% soil moisture content), respectively. The experimental results can provide basic data and technical support for the development of non-contact wheat seeding equipment in rice-wheat rotation area.Keywords: pneumatic seeding, loam clay, soil adhesion, wheat, high-speed photographyDOI: 10.25165/j.ijabe.20201301.4906Citation: Wang C, Lu C Y, Li H W, He J, Wang Q J, Cheng X P. Preliminary bench experiment study on working parameters of pneumatic seeding mechanism for wheat in rice-wheat rotation areas. Int J Agric & Biol Eng, 2020; 13(1): 66–72.